Proceedings of the Fifth International Conference on Machine Learning : June 12-15, 1988, University of Michigan, Ann Arbor, Michigan - Laird, John, 1954- (Proceedings - international conference on machine learning, 1988)
Machine Learning Proceedings 1988.